Inklusi Keuangan Syari’ah di Malaysia: Peran Tadika Al-Fikh Orchard, Malaysia dalam Edukasi Keuangan Dini - Tri Novita Syahfitri; Alfi Amalia (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The low level of knowledge and adequate ability of society in managing finances, which will give rise to problems such as debt, inflation and economic instability, is mainly caused by a lack of effective education. Even though sharia financial inclusion is important to increase public awareness and participation in the sharia financial system, sharia financial education is still not widely implemented in Malaysian schools, due to limited resources, teacher capabilities and community awareness. Low levels of public understanding also have an impact on weak self-control abilities and the potential for high levels of debt. This research aims to describe the role of Tadika Al-Fikh Orchard, Malaysia in early sharia financial education. The main focus is to find effective strategies to provide sharia-based financial education to young children and increase sharia financial inclusion in Malaysia. This research uses a qualitative descriptive method, the research subjects are teachers and children in Tadika Al-Fikh Orchard, Malaysia. Data collection was carried out through in-depth interviews, direct observation and documentation. The results of the research show that the sharia financial education program with a fun and creative approach applied is very effective in describing the level of sharia financial inclusion for young children.